A Survey and Analysis of the American Public's Perceptions and Knowledge About Antibiotic Resistance. (30th May 2016) - Carter, Rebecca R.; Sun, Jiayang; Jump, Robin L. P.
Abstract : A crowdsourced survey found that most Americans are aware that antibiotic misuse contributes to antibiotic resistance. The survey also found that Americans are less aware that antibiotic resistance is a significant problem and of the biologic mechanisms of bacterial resistance. Abstract: Background.  Little is known about the American public's perceptions or knowledge about antibiotic-resistant bacteria or antibiotic misuse. We hypothesized that although many people recognize antibiotic resistance as a problem, they may not understand the relationship between antibiotic consumption and selection of resistant bacteria. Methods.  We developed and tested a survey asking respondents about their perceptions and knowledge regarding appropriate antibiotic use. Respondents were recruited with the Amazon Mechanical Turk crowdsourcing platform. The survey, carefully designed to assess a crowd-sourced population, asked respondents to explain "antibiotic resistance" in their own words. Subsequent questions were multiple choice. Results.  Of 215 respondents, the vast majority agreed that inappropriate antibiotic use contributes to antibiotic resistance (92%), whereas a notable proportion (70%) responded neutrally or disagreed with the statement that antibiotic resistance is a problem. Over 40% of respondents indicated that antibiotics were the best choice to treat a fever or a runny nose and sore throat. Major themes from the free-text responses included that antibiotic resistance develops by bacteria, or by the infection, or the body (ie, an immune response). Minor themes included antibiotic overuse and antibiotic resistance caused by bacterial adaptation or an immune response. Conclusions.  Our findings indicate that the public is aware that antibiotic misuse contributes to antibiotic resistance, but many do not consider it to be an important problem. The free-text responses suggest specific educational targets, including the difference between an immune response and bacterial adaptation, to increase awareness and understanding of antibiotic resistance.